Pelatihan Strategi Menarik Konsumen Melalui Konten Media Sosial pada Pelaku Usaha - Abdurrahman, Abdurrahman; Irany, Raden Bagus Faizal; Kurniawan, Dedi; Dakwah, Mujahid Mujahid; Rinuastuti, Baiq Handayani (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2023)
Social media content strategy training has become a necessity for business owners in the rapidly evolving digital era. The aim of this training is to help business owners understand more effective ways to promote their products or services through social media. In Mataram, this training has had a positive impact on business owners. During the training, participants are taught how to create content that is engaging and relevant to their target market. In addition, the training also helps business owners understand social media data analysis, so they can measure the effectiveness of their campaigns and make more informed decisions in their marketing strategies. As a result of this training, business owners in Mataram can expand their market reach, increase brand awareness, and boost sales. However, it should be noted that this training is not an instant solution to all marketing problems. It takes time and effort to build a strong and consistent online presence, as well as continuously updating marketing strategies to keep up with changing trends and market needs.